A circularly polarized folded reflectarray antenna for Ka‐band satellite communications uplinks. Issue 4 (12th May 2022) - Zhang, Pan‐Pan; Zhu, Xi‐Cheng; Shu, Xiao‐Le; Wu, Xiao‐Hu; Jiang, Mei; Ge, Jun‐Xiang
Abstract: A low‐profile circularly polarized folded reflectarray antenna (CPFRA) with linearly polarized (LP) feed antenna is presented in this article. Polarizing grid usually used as the subreflector of traditional FRA is replaced by a polarization‐sensitive frequency selective surface (FSS) in the CPFRA design. The polarization‐sensitive FSS is designed to convert the LP incidence into the CP wave within its passband while reflecting the orthogonal LP incident wave over its operating frequency band. A CPFRA prototype has been proposed and validated for Ka band satellite communications uplinks in this article. The maximum measured antenna gain of 26.0 dBic is achieved at 29.75 GHz with the corresponding antenna aperture efficiency of 40%. Beam scanning property has been achieved by the CPFRA with the mechanical movement of feed horn antenna. All the measured axial ratios (ARs) of the CPFRA are lower than 3 dB in the frequency range from 29 to 30.25 GHz. Meanwhile, the measured antenna gain variation with different beam scanning angles is less than 1 dB from 29.25 to 31 GHz.